Rumen microbiota responses to the enzymatic hydrolyzed cottonseed peptide supplement under high-concentrate diet feeding process - Ma, Peng; Hong, Yifen; Liu, Chunxue; Sun, Yuqin; Liu, Minze; Yang, Zhengang; Ma, Pengyun; Wu, Hongxiang; Xue, Fuguang (Frontiers in Veterinary Science, 2022)
In current dairy production, dietary energy is always excessively provided with high-concentrate diet feeding to improve milk production. However, this feeding practice disturbed the rumen microbial ecosystem and the balance between ruminal energy and nitrogen, resultantly decreased the nutrients fermentability, which in turn declined the milk yield of dairy cows. Therefore, supplement of dietary degradable nitrogen may be helpful for high dairy production. In this study, we evaluated the regulatory effects of easy-utilized enzymatic hydrolyzed cotton-seed peptides (EHP) supplements on rumen microbiota communities and rumen nutrients fermentability under high concentrate feeding. For this purpose, gradient concentrate of EHP (from 0.2%-1.0%) was added into the high-concentrate basal substrates for an in vitro experiment. Each treatment contained 3 replicates, with 3 bottles in each replicate. Rumen fermentable parameters included microbial protein content, volatile fatty acids, and ammonia-N; rumen nutrients degradability included dry matter, crude protein, neutral detergent fiber, acid detergent fiber, ether extracts, calcium, and phosphorus were further investigated after in vitro fermentation for 72 hours. Following, rumen microbiota communities and their correlation with ruminal fermentation parameters and rumen nutritional degradability were analyzed to decipher the regulatory mechanism of the EHP supplements on rumen fermentability. Results indicated that treatment with 0.6% of EHP supplement had the highest content of acetate, butyrate, and neutral detergent fiber degradability among all treatments. Further, EHP supplement significantly increased the relative abundances of rumen cellulose and starch degrading bacteria which included Ruminococcus, Bifidobacterium, and Acetitomaculum, and the high nitrogen utilized bacteria Butyrivibrio and Pseudobutyrivibrio, which may further promote the rumen carbohydrate and nitrogen metabolism. In summary, supplemented with easy degraded small peptide help re-establish of rumen energy and nitrogen balance to promote the rumen fermentable functions and nutritional degradability under high concentrate diet feeding circumstance. These findings may further promote dairy production.